The two Frank Thrings - Fitzpatrick, Peter (Monash Univ. Publ., 2012)
They shared a name, of course, and their physical resemblance was startling. And both Frank Thrings were huge figures in the landscape of 20th century Australian theatre and film. This compelling dual biography is a kind of detective story, following the lives of two men who did all they could to cover their tracks, and to conceal the self